Distribución en el campo y en la planta de Unaspis citri C. (Homoptera: Dispididae) - Fernández, M.=700 1 González, C.
(Es, En)
Ilus., 9 ref.
Keywords: UNASPIS; DISTRIBUCION DE LA POBLACION; EXPERIMENTACION EN CAMPO; CITRUS SINENSIS; UNASPIS CITRI; DISTRIBUCION ESPACIAL; CITRUS LATISFOLIA